Screened encounters : the Leipzig documentary film festival, 1955-1990 - Moine, Caroline 1973- (Film and the global cold war, 2018)
Established in 1955, the Leipzig Film Festival's location in the German Democratic Republic deeply implicated it in cultural and political competition between East and West Germany, opening a political and artistic exchange that would have otherwise been impossible. Screened Encounters represents the definitive history of this key event, recounting its history from its founding until reunification, and tracing the outsize influence it exerted on international cultural relations during the Cold War